Pengaruh Orientasi Kewirausahaan, Kapabilitas Inovasi Dan Payment Gateway Terhadap Kinerja Usaha UMKM Kuliner Merchant Elektronik Payment System Di Kabupaten Bekasi - Ameliana, Ameliana; Junedi, Junedi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Business competition is getting tighter today, especially in the increasing culinary field. This study aims to analyze how the influence of Entrepreneurial Orientation, Innovation Capability and Payment Gateway on business performance in MSMEs Culinary Electronic Merchant Payment System in Bekasi Regency. The sample in this study was 100 MSME business actors Culinary Electronic Payment System Merchants in Bekasi Regency. Data collection method through the distribution of questionnaires to respondents as research objects. Data analysis techniques use multiple linear regression tests, hypothesis tests using t tests and determination coefficient tests.  The results of this study are (1) There is an influence of entrepreneurial orientation on business performance obtained tcount= (16.772) > ttable (1.986) so that H1 is accepted. (2) There is no effect of innovation capability on business performance obtained tcount (0.154) < ttable (1.986) so that H2 is rejected. There is an influence of payment gateways on business performance obtained t count (2,313) > t table (1,986) so that it can be concluded that H3 is accepted. The conclusion of this study is that the variables of entrepreneurial orientation and payment gateway affect business performance, while innovation capabilities do not affect the business performance of MSMEs Culinary Electronic Merchant Payment System in Bekasi Regency.